The Vindication of Eros in the Age of Enlightenment: Los besos de amor by Juan Meléndez Valdés - Philip DEACON (Cuadernos Dieciochistas)
The article attempts to demonstrate how, in eighteenth-century Europe, certain literary texts with an erotic subject matter belong to the change in thinking and practices associated with the Enlightenment. The argument begins with an examination of how ideas relating to human sexuality contribute to a new vision of humanity grounded in Enlightenment thought. Links are made between theorizing elsewhere in Europe and the expression of concepts of sexuality at variance with official thinking in Spain but which can be observed in cases preserved in Inquisition files. Having established this intellectual and cultural framework, the collection of poems entitled Los besos de amor by Juan Meléndez Valdés is analysed in an attempt to demonstrate how the author’s exploration of human sexuality defies the restrictions placed on such writings by the Spanish Inquisition, with the result that Meléndez’s verses could not be published in his lifetime.